Kritik terhadap Rezim Kebijakan Pertanian Negara Maju dan Dampaknya terhadap Indonesia - Ibnu, Muhammad (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2025)
Abstract. This study examines how agricultural policy regimes developed by the United States, the European Union, and New Zealand since the end of World War II have contributed to structural inequalities in the global food system, particularly in relation to developing countries such as Indonesia. The primary focus is a critical analysis of moral narratives—such as hunger alleviation—used to legitimize protectionist policies, including export-based food aid in the United States, multifunctional subsidies in the European Union, and market liberalization in New Zealand. Employing a historical-political approach and critical policy analysis and supported by a systematic literature review following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, this study reveals how these policies reinforce the dominance of developed countries in global food governance while undermining food sovereignty in the Global South. The findings underline the urgency for Indonesia to formulate agricultural policies that are locally grounded, socially just, and environmentally sustainable. Approaches such as agroecology, agrarian reform, and protections for smallholder farmers are proposed as more contextually a